0565 Obstructive Sleep Apnea, But Not Short Sleep Duration, is Independently Associated with Insulin Resistance: A Large-Scale Cohort Study. (27th May 2020) - Yin, S; Xu, H; Zou, J; Zhang, C; Guan, J; Yi, H
Abstract: Introduction: Both short sleep duration and obstructive sleep apnea (OSA) seem to be associated with insulin resistance. However, the majority of previous studies addressing the relationship between OSA and insulin resistance did not evaluate short sleep duration, and vice versa. In this study, we used a large-scale hospital-based cross-sectional dataset, including 5, 447 participants, to examine 1) whether objectively measured short sleep duration and OSA are independently associated with insulin resistance, and 2) whether the presence of OSA modulates the association between sleep duration and insulin resistance. Methods: Participants were consecutively enrolled from our sleep center during the period from 2007 to 2017. The index of homeostasis model assessment insulin resistance (HOMA-IR) was calculated from insulin and glucose. Sleep duration was determined by standard polysomnography. The associations between sleep duration and insulin resistance were estimated by logistic regression analyses. Results: A total of 5, 447 participants (4507 OSA and 940 primary snorers) were included in the study. In comparison to primary snorers, OSA combined with extremely short sleep duration (< 5 hours) increased the risk of insulin resistance by 34% (OR, 1.34; 95% CI, 1.01-1.77) after adjusting for confounding factors that are frequently associated with insulin resistance and OSA. In subgroup analysis stratified by sleep duration, the risk of insulin resistance in patients with a short sleep duration (5-6 hours or < 5 hours) was increased in those with OSA compared to primary snorers, but not in the other three sleep duration groups (6 - 7, 7 - 8, and > 8 hours). Conclusion: OSA, but not short sleep duration, was independently associated with insulin resistance. It is worth noting that OSA combined with extremely short sleep duration showed a greater detrimental effect than OSA itself with regard to insulin resistance. Support: This study was supported by grants-in-aid from Shanghai Municipal Commission of Science and Technology (Grant No.18DZ2260200).